Do TripAdvisor Valences are Trustworthy on South Asian Destinations? - Senthil Veerasamy; Susobhan Goswami; Kandappan Balasubramanian (ASEAN Journal on Hospitality and Tourism, 2023)
Travellers prefer to rely on peers’ recommendations and review websites to look for reliable and unbiased information. Trustworthy communicators are more influential than the untrustworthy one. Trustworthy content is need of the hour in specific to post COVID19 travel. This research is analysing what propels a traveller towards destinations and empirically verify the valences of trustworthiness on TripAdvisor reviews.  Content analysis of TripAdvisor reviews (153799 numbers) on South Asian destinations are captured, modelled, and analysed using Descriptive statistics, Regression Analysis and Structural Equation Modelling. Positive reviews are more trustworthy than the negative reviews and are helpful to potential tourist who seeks ‘real’ or ‘genuine’ reviews. There is no moderating effect of negative sentiments on Trustworthiness. Our research results find that valences of TripAdvisor review are useful to potential tourists for their travel planning and actions. Practitioners should listen to TripAdvisor review valences and keep up with the value chain, make the destinations more tourist friendly and evolve new themes. Tourism ecosystem should use modicum of digital opportunities emanating from sentiments and apply appropriate strategies to develop their destinations. This way, tourists will develop brand equity. This study contributes to the growing body of literature on polarity analysis in TripAdvisor reviews and investigated the relationship between positive and negative valences with trustworthiness.